2020
DOI: 10.1111/evj.13218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a propriety oiled mixed hay feeding system on lung function, neutrophilic airway inflammation and oxidative stress in severe asthmatic horses

Abstract: Background Hay feeding is considered the main triggering factor for airway obstruction and inflammation in severe equine asthma (SEA). Finding alternate strategies allowing hay feeding while controlling clinical signs of SEA is of importance. The Nutri‐Foin Système is believed to decrease inhaled dust by incorporating soybean oil to mechanically processed hay. Objectives We compared airflow obstruction and airway inflammation in horses with SEA fed oiled hay or alfalfa pellet regimen. Study design Controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 33 publications
0
18
0
5
Order By: Relevance
“…It also was not possible to impute causality to our observations, especially because exacerbation of asthma in horses is intrinsically linked to a change in diet. This could change in the future, by inducing exacerbation without changing the diet with methods using hay mixed with oil to maintain horses in remission thus decreasing inhaled antigens without changing the type of diet …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also was not possible to impute causality to our observations, especially because exacerbation of asthma in horses is intrinsically linked to a change in diet. This could change in the future, by inducing exacerbation without changing the diet with methods using hay mixed with oil to maintain horses in remission thus decreasing inhaled antigens without changing the type of diet …”
Section: Discussionmentioning
confidence: 99%
“…This could change in the future, by inducing exacerbation without changing the diet with methods using hay mixed with oil to maintain horses in remission thus decreasing inhaled antigens without changing the type of diet. 31…”
Section: Limitationsmentioning
confidence: 99%
“…Stables compromise both physical and visual contact and frequently have poor circulation and air quality, with high ammonia concentrations, and dust/moulds from hay, straw and bedding. The respiratory system of the horse is compromised [ 51 ] and obstructive pulmonary disease may ensue [ 52 ]. Huffman [ 51 ] suggested that adequate ventilation should be mandatory in all new stabling, including ceiling fans.…”
Section: Discussionmentioning
confidence: 99%
“…In the 19th century rail travel became increasingly popular for moving horses but it is now common to fly racehorses to interstate race meetings. Dehydration and weight loss are risks in all long distance transport, as is Shipping Fever caused by a horse’s head being tied in such a way as to prevent it being lowered or raised, thus preventing effective draining of the upper respiratory tract [ 52 ]. Shipping fever is also a major concern with air transportation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 But the resolution of neutrophilic inflammation may require months of low-dust conditions. 9,10 Airway inflammation in human asthmatics is thought to reflect a failure to resolve inflammation, thereby preventing a return to homeostasis after an inflammatory trigger. 11 The fatty acid composition of an individual's diet influences the formation of inflammatory mediators related to many chronic diseases, such as…”
mentioning
confidence: 99%